Valorization of sugarcane bagasse for sugar extraction and residue as an adsorbent for pollutant removal - Wang, Duanhao; Tian, Jiahua; Guan, Jian; Ding, Yiwen; Wang, Ming Li; Tonnis, Brandon; Liu, Jiayang; Huang, Qingguo (Frontiers in Bioengineering and Biotechnology, 2022)
Following juice crushing for sugar or bioethanol production from sugarcane, bagasse (SCB) is generated as the main lignocellulosic by-product. This study utilized SCB generated by a hydraulic press as feedstock to evaluate sugar extraction as well as adsorption potential. Total soluble sugar (sucrose, glucose, and fructose) of 0.4 g/g SCB was recovered with H2O extraction in this case. Insoluble sugar, that is, cellulose in SCB, was further hydrolyzed into glucose (2%–31%) with cellulase enzyme, generating a new bagasse residue (SCBE). Persulfate pretreatment of SCB slightly enhanced saccharification. Both SCB and SCBE showed great potential as adsorbents with 98% of methylene blue (MB) removed by SCB or SCBE and 75% of Cu2+ by SCBE and 80% by SCB in 60 min. The maximum adsorption amount (qm) was 85.8 mg/g (MB by SCB), 77.5 mg/g (MB by SCBE), 3.4 mg/g (Cu2+ by SCB), and 1.2 mg/g (Cu2+ by SCBE). The thermodynamics indicated that the adsorption process is spontaneous, endothermic, and more random in nature. The experimental results offer an alternative to better reutilize SCB.